THE EFFECTIVENESS OF THE MINISTER OF COMMUNICATION AND INFORMATICS REGULATION NUMBER 20 OF 2016 ON THE PROTECTION OF PERSONAL DATA IN ELECTRONIC SYSTEMS - Ash Shiddiq, Fadhilah Pijar; Rosadi, Sinta Dewi; Permata, Rika Ratna (Yustisia, 2019)
Privacy, as a part of Human Rights, is the right of freedom of private matters. The basic concept of privacy is “the right to be let alone” which state that every individual have the right to have his own solitude without intervention. One of the most important information which also can be associated with Information Privacy is Personal Data that shall be protected as a form of protection to the privacy itself. Some of the personal data has been used as the requirements of the SIM Card Registration, thus making new problems regarding its personal data protection since the comprehensive regulation still covered only by the Ministral Regulation. Research method used in this paper is Descriptive Analytic in which the writer analyze the research object by explaining the situation and the condition of the personal data protection obtained from literatures on the facts that can be associated with the implementation of SIM Card Registration Policy according to Indonesia’s Positive Law and International Law. According to the result of the study, the Ministral Regulation already covered most of the basic data protection needed in the SIM card registration policy, however the protection provided by the Ministral Regulation still has not covered the third party involved. The Involvement of this third party is inevitable and should be protected immediatelyin order to prevent any abuse of personal data.